P247 The respiratory phenotype of the BBS4 null mouse lung. (2nd December 2011) - Cho, M; Beales, P; Hind, M; Quinlan, R
Abstract : Introduction: Bardet–Biedl Syndrome (BBS) is an autosomal recessive disorder due to BBS gene mutations that result in primary ciliary dysfunction (Hildebrandt et al, N Engl J Med 2011). Primary cilia are found on most eukaryotic cells and have been reported in various human organs including kidneys, brain, and lung airways. BBS patients present with a number of features including polydactyly, obesity, visual impairment and renal cysts and these are also seen in other examples of ciliopathies. Many BBS patients report frequent respiratory infections and are empirically diagnosed with asthma; yet, little is known about the pulmonary effects of BBS and explanations for the respiratory presentations remain unclear. We have recently described the respiratory phenotype of a cohort of 28 consecutive BBS patients (Hind: unpublished data). This study investigates whether there are structural and functional defects in the BBS lung that may explain the frequent respiratory symptoms described by BBS patients. Methods: Lungs from Bbs4 null mice (Bbs4−/−) were examined and compared to unaffected control littermates. Lung volumes were measured by volume displacement and alveolar tissue assessed through morphometry according to ATS/ERS standards (Hsia, AJRCCM, 2010). These data were used to derive the alveolar surface area (Sa) for each animal. Functional studies of motile cilia using ciliary beat frequency (CBF) and inflammatory cell types in the distal lungs were analysed both from bronchoalveolar lavage fluid (BALF) and using immunohistochemistry on lung sections. Results: We show that, as seen in the heterogeneous patient group, the Bbs4−/− mice are significantly heavier than control littermates. Lung volume and Sa of all mice increase with age; however, Bbs4−/− mice have smaller lung volumes and a reduced Sa. Furthermore, lung histology demonstrates that Bbs4−/− mice show evidence of chronic infection. Although we have not found any evidence for ultrastructural defects in airway motile cilia, Bbs4−/− null mice have a significantly slower CBF. Conclusion: These data suggest that a loss of function in BBS4 results in a greater body mass, a functional motile ciliary defect, frequent inflammation, and reduced gas-exchanging surface area of the lung.